The Implementation of Project Based Learning to Improve Students’ Achievement and Motivation in the Speaking Class at Tenth Grade Vocational High School - Karsimah; Eni Rahayu Puji Haryanti; Widhiyanto (Universitas Islam Negeri Palopo, 2025)
This study was intended to find out whether the Project-Based Learning implementation is effective in improving students’ speaking skills. The researcher employed a combination of quantitative and qualitative research methods, including pre- and post-tests, to assess students’ productive skills, particularly in speaking. Besides, the researcher interviewed the teacher and the students to ask their perceptions of the implementation of project-based learning. There were 20 students as the respondents. Tenth-grade students of SMK TKJ Nurul Islami became the experimental class. The mean score showed that the pretest was 51.18. On the other hand, the mean score of the posttest was 78. The percentage and frequency of students' scores on the pretest for the experimental class showed that six students, or 35%, received an average score, while fourteen students, or 84%, received a poor score. However, after implementing the project-based learning method in the classroom, the results improved. In the posttest, four students (24%) achieved very good scores, eight students (47%) received good scores, and eight students (47%) received average scores. There was a significant difference between the pretest and the posttest. Based on the result, there was a significant difference between the experimental class in their speaking achievement. It means that the implementation of Project-Based Learning was beneficial in improving students' speaking ability in reporting descriptive text.